Usability of organic resin-based manganese-added methyl ester oil produced from Sardine fish waste as an alternative fuel in diesel engine - Üstün, Süleyman (CT&F - Ciencia, Tecnología y Futuro, 2021)
This paper deals with the usability of sardine fish oil methyl ester doped with manganese based organic compound in diesel engines as an alternative fuel. For this purpose, raw sardine fish oil was obtained from sardine fish waste (fish heads, fish bones, and fish internal organs). A two-step catalytic process was performed to convert the raw sardine fish oil into methyl ester. Methanol, sulfuric acid and sodium hydroxide catalysts were used for the reaction. The quality of biodiesel produced in this study agrees with the Standard Specification for Biodiesel Fuel American Society for Testing and Materials (ASTM 6751). Smn50, Smn75, and Smn100 experimental fuels were obtained by mixing the obtained fish oil methyl ester into diesel fuel (DF) at 50%, 75%, and 100% by volume. Then, 12 ppm organic resin-based manganese (Mn) was added to each mixture. The obtained fuel mixtures were tested and compared with pure diesel fuel (DF) under full-load engine torque condition in terms of engine performance and emissions. The results show that the temperatures of exhaust and engine torque, power, NOx, CO2 decrease when Mn-added biodiesel blends are used on the engine. Compared to other fuel blends, the Smn50 fuel blend underwent the greatest reduction. In the Smn50 fuel mixture, on average, a decrease of 11.64% in torque, 11.16% in power, 10.06% in NOx, 1.25% in CO2, and 1.05% in exhaust gas temperature was observed. On the other hand, BSFC, HC, CO emission values were higher than diesel fuel. The least increase in these values was observed in the Smn50 fuel mixture. In Smn50 fuel, on average, the increase was 20.90% in BSFC, 4.22% in CO and 13.40% in HC.